Alkaline thermal pretreatment of waste activated sludge for enhanced hydrogen production in microbial electrolysis cells. (15th September 2021) - Wang, Heming; Liu, Jidong; Zhang, Zizhen; Li, Juanjuan; Zhang, Huihui; Zhan, Yali
Abstract: Resource utilization of waste activated sludge (WAS) has become a mainstream development direction. Alkaline thermal pretreatment (TPT) was found to greatly promote the bioaccessibility and biodegradability of the sludge. The organic matter including soluble chemical oxygen demand (SCOD), soluble carbohydrate, soluble protein and volatile fatty acids (VFAs) after low temperature (90 °C) pretreatment was 4.8%–65.9% higher than that after high temperature (180 °C) pretreatment. These increasements could be contributed by the alkaline treatment condition and the longer treatment time. The alkaline condition reduced the resistance of cell wall to the temperature. The pretreatment time at 90 °C was two times of that at 180 °C, allowing more organic matter to be released. But the total energy consumption of low temperature pretreatment (2580.7 kJ/L) was 30.5% lower than that of high temperature pretreatment (3711.8 kJ/L). The sludge fermentation liquid (SFL) was then employed as the substrate in microbial electrolysis cells (MECs), and the utilization efficiency of acetic acid was the highest (74.9%–83.2%). The hydrogen yield using low temperature pretreated sludge was 0.44 m 3 /(m 3 ·d), which was higher than that of using high temperature pretreated sludge (0.31 m 3 /(m 3 ·d)). These results suggested that alkaline TPT at 90 °C was an effective way to hydrolyze sludge and further enhance hydrogen production in MECs. Highlights: Alkaline hydrothermal pretreatment is effective to improve sludge biodegradability. The low temperature pretreatment consumes less energy to hydrolyze sludge. Hydrogen production is significantly increased in MECs fed with pretreated sludge.